Development of a Nursing protocol for childcare consultations - Gubert, Fabiane do Amaral; Santos, Daisyanne Augusto dos Sales; Pinheiro, Maria Talyta Mota; Brito, Larissa Ludmila Monteiro de Souza; Pinheiro, Sarah Rayssa Cordeiro Sales; Martins, Mariana Cavalcante (Rev Rene, 2015)
Objective: to present a Nursing protocol for childcare consultations based on the Nursing Model of Roper-Logan-Tierney. Methods: for its development, the following items were carried out: literature review, selection and reading of materials considered important in the area of children’s health. Results: it was carry out the textual development of the protocol divided into five chapters, according to milestones of the infant’s growth and development; inclusion of variables – protocol questions, separated according to life activities recommended in the Nursing model; and content evaluation by nine investigators using the Content Validity Index, with most items presenting an index greater than 0.80. Conclusion: the produced protocol is relevant to support childcare Nursing consultations, enabling standardized directed care and comprehensive care of children’s health in their first months of life.